Accessing Students' Reasoning for Disengagement. (1st July 2011) - Deed, Craig
This paper examines what students can tell us about their strategic decision to engage or disengage from learning. A means of accessing student knowledge and experience about teaching and learning is explicated, along with a discussion of student reasoning for making an investment in learning. It is argued that disengagement is a reasoned decision based on questions of relevance, usefulness and student capacity to be successful.